Utilization of Sugars in Hydrolysate from Oil Palm Empty Fruit Bunches for Ethanol Fermentation using Pichiastipitis CBS 5773 - Herri Susanto; Achmad Ali Syamsuriputra (ASEAN Journal of Chemical Engineering, 2004)
The utilization of pentose derived from hydrolysis of oil palm empty fruit bunches (EFB) were studied using (a) acid hydrolysis at a mild condition, (b) detoxification of hydrolysate containing pentose, (c) cell growth, and (d) fermentation to produce ethanol. Although Saccharomyces cerevisiae and Pichia stipitis were observed to be able to metabolize pentose in the hydrolysate derived from EFB, only Pichia stipitis was able to produce ethanol. When xylose was used as a model compound for pentose, the optimum xylose concentration for fermentation was 30 glL with the ethanol concentration in fermentation broth upto 13 g/L. Fermentation with higher xylose concentrations produced ethanol with a concentration of about 6 glL. Fermentation using pentose derived from detoxified hydrolysate could produce ethanol with a concentration in fermentation broth of about 3 g/L.